Evaluating the anxiety and nursing care satisfaction of the patients in internal medicine and surgical services (Annals of Medical Research, 2021)
Aim: This cross-sectional and analytical study was conducted with the aim of evaluating the anxiety and nursing care satisfaction of the patients in internal medicine and surgical services.Materials and Methods: This study was conducted between January and March 2018 in the internal medicine and surgery clinics of a Training and Research Hospital in Turkey. Data were collected using the Patient Information Form, the Beck Anxiety Inventory (BAI) and the Newcastle Satisfaction with Nursing Scale (NSNS). Descriptive statistics, Kolmogorov-Smirnov test, Mann Whitney U test and Kruskal Wallis test were used in data analysis.Results: The mean total NSNS score was 57.06 ± 6.07, and the mean BAI score was 13.00 ± 12.91. The BAI and NSNS scores were negatively correlated (r = -0.239, p < 0.05). It was found that low anxiety scores were associated with being satisfied with patient-nurse communication, being satisfied with treatment, and care information and having a nuclear family (p < 0.05). NSNS scores were significantly correlated with family structure, patient-nurse communication, pre-treatment information, and satisfaction level at thetime of discharge (p < 0.05).Conclusions: There is a negative correlation between the anxiety and nursing care satisfaction of the patients. This suggests that  enhanced communication and attention, especially prior to any medical intervention, provides better feedback and improves patient satisfaction levels.
Keywords: Hospital; medical services; nursing care; nurse; patient; satisfaction; surgical services